Social exploitation of extensive, ephemeral, environmentally controlled prey patches by supergroups of rorqual whales. (December 2021) - Cade, David E.; Fahlbusch, James A.; Oestreich, William K.; Ryan, John; Calambokidis, John; Findlay, Ken P.; Friedlaender, Ari S.; Hazen, Elliott L.; Seakamela, S. Mduduzi; Goldbogen, Jeremy A.
Abstract : Large groups of animals aggregate around resource hotspots, with group size often influenced by the heterogeneity of the environment. In most cases, the foraging success of individuals within groups is interdependent, scaling either constructively or destructively with group size. Here we used biologging tags, acoustic prey mapping, passive acoustic recording of social cues and remote sensing of surface currents to investigate an alternative scenario in which large, dense aggregations of southeast Atlantic humpback whales, Megaptera novaeangliae, and northeast Pacific blue whales, Balaenoptera musculus, were each associated with ephemeral krill aggregations large enough such that their availability to predators appeared to be influenced more by environmental features than by consumption, implying independence of group size and consumption rates. We found that the temporal scale and spatial extent of oceanographic drivers were consistent with the temporal scale and locations of predator aggregations, and additionally found that groups formed above bathymetric features known to promote zooplankton concentration. Additionally, we found calling behaviour counter-indicative of competition: blue whale foraging calls were anomalously high during observed aggregation time periods, suggesting signalling behaviour that could alert conspecifics to the location of high-quality resources. Modelled results suggest that the use of social information reduces the time required for individuals to discover and exploit high-quality resources, allowing for more efficient foraging without apparent costs to the caller. Thus, rorqual whales foraging in these environments appear to exhibit a social foraging strategy whereby a behaviour with negligible individual costs (signalling) provides information that enhances group foraging efficiency. The population density dependence of this social foraging strategy may help explain why some rorqual species were at first slow to recover from human exploitation, but have since increased more rapidly. Highlights: Large, dense prey patches were found near supergroups of rorqual whales. Ephemeral patches formed when surface features intersected with bathymetry. Blue whales increased social call production during observed aggregation events. Rorqual whale foraging appears to be enhanced when social information is utilized.